Perancangan Company Profile Berbasis Web Pada Pondok Pesantren Salafiyah Syamsul Huda Batam - Stefanus Eko Prasetyo; Muhammad Yaasin (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Pondok Pesantren Salafiyah Syamsul Huda Batam is a boarding school engaged in social, educational, and religious affairs located in Tiban Satu Complex, Sekupang District, Batam. This organization has problems in the marketing process in finding new students who still use brochures. Therefore, this organization needs a web-based company profile to increase efficiency for marketing. The method for designing such a website is sdlc method. The result of this design is in the form of a company profile website. The website also aims as a means of digital marketing.